2012
DOI: 10.1128/aem.06183-11
|View full text |Cite
|
Sign up to set email alerts
|

Casuarina Root Exudates Alter the Physiology, Surface Properties, and Plant Infectivity of Frankia sp. Strain CcI3

Abstract: The actinomycete genus Frankia forms nitrogen-fixing symbioses with 8 different families of actinorhizal plants, representing more than 200 different species. Very little is known about the initial molecular interactions between Frankia and host plants in the rhizosphere. Root exudates are important in Rhizobium-legume symbiosis, especially for initiating Nod factor synthesis. We measured differences in Frankia physiology after exposure to host aqueous root exudates to assess their effects on actinorhizal symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…This finding is in accordance with the reports of the bacterial microbiota of the coastal halophytes Limonium vulgare (39) and Messerschmidia sibirica (40). This is probably due to the exudates secreted by plant roots, which could be used as carbon and nitrogen sources for bacterial growth in the rhizosphere (41).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with the reports of the bacterial microbiota of the coastal halophytes Limonium vulgare (39) and Messerschmidia sibirica (40). This is probably due to the exudates secreted by plant roots, which could be used as carbon and nitrogen sources for bacterial growth in the rhizosphere (41).…”
Section: Discussionsupporting
confidence: 92%
“…Root exudates play an important role in Rhizobium –legume interactions, particularly for initiating synthesis of proteins required for nodulation (Nod factors). Root exudates were collected from C. cunninghamiana plants grown under nitrogen‐sufficient and nitrogen‐deficient conditions and tested on Frankia strain CcI3 (Beauchemin et al ., ). The presence of root exudates increased the growth of Frankia CcI3, but the strain could not use the root extract as the sole carbon source.…”
Section: The Host Plants – Actinorhizal Plantsmentioning
confidence: 97%
“…These two results suggest that the presence of root extracts caused a chemotrophic response and/or changes in the surface properties of the bacteria at the fatty acid level. In addition, plants inoculated with Frankia previously exposed to root extracts nodulated after 15 days, while plants inoculated with unexposed Frankia nodulated only after 19.6 days (Beauchemin et al ., ). Physiological changes to Frankia from host root exudates were therefore beneficial to the infection and nodulation process.…”
Section: The Host Plants – Actinorhizal Plantsmentioning
confidence: 97%
“…23 In the case of actinorhizal symbiosis, Frankia signals are unknown. 24,25 However, it has been previously shown that Frankia alni (ACN14a) produces a root hair deforming factor (RHDF) in culture supernatant that reacts with Alnus glutinosa root hair cells inducing branching and curling of root hair cells. 26 This factor was shown to have a molecular weight below 3,000 da, to be heat-stable (similar to Rhizobium Nod factor) but also to be hydrophilic and to resist to chitinases (contrary to Rhizobium Nod factor).…”
Section: The Role Of Flavonoids In the Establishment Of Plant Roots Ementioning
confidence: 98%